2010
DOI: 10.1016/j.jmb.2010.08.045
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Hinge in Eukaryotic MutY Homologues Mediates Catalytic Activity and Rad9–Rad1–Hus1 Checkpoint Complex Interactions

Abstract: The DNA glycosylase MutY homologue (MYH or MUTYH) removes adenines misincorporated opposite 8-oxoguanine as part of the base excision repair pathway. Importantly, defects in human MYH (hMYH) activity cause the inherited colorectal cancer syndrome, MYH-associated polyposis (MAP). A key feature of MYH activity is its coordination with the cell cycle checkpoint via interaction with the Rad9-Rad1-Hus1 (9-1-1) complex. The 9-1-1 complex facilitates cell cycle checkpoint activity and coordinates this activity with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(111 citation statements)
references
References 64 publications
4
107
0
Order By: Relevance
“…Recently, it has been reported that ATR phosphorylation upon HU or UV treatment was decreased in hMYH-disrupted HEK293 and HaCaT cells (14). ATR is known to phosphorylate Chk1 and Chk2 (14,15), and here, we observed a phosphorylation of Chk2 only in control-transfected cells, but not in siMYH cells following ETP treatment (Fig. 2A).…”
Section: Effect Of Etp On Hek293 Cell Proliferationsupporting
confidence: 67%
See 1 more Smart Citation
“…Recently, it has been reported that ATR phosphorylation upon HU or UV treatment was decreased in hMYH-disrupted HEK293 and HaCaT cells (14). ATR is known to phosphorylate Chk1 and Chk2 (14,15), and here, we observed a phosphorylation of Chk2 only in control-transfected cells, but not in siMYH cells following ETP treatment (Fig. 2A).…”
Section: Effect Of Etp On Hek293 Cell Proliferationsupporting
confidence: 67%
“…Furthermore, in hMYH-disrupted cells, the phosphorylation of ATR and Chk1 is decreased by hydroxyurea (HU) or ultraviolet (UV) treatment (14). The hMYH is known to interact with 9-1-1 (15), and a recent study revealed that it also interacts with ATR and MutS α via the human MutS homolog (hMSH) 6 subunit (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both germline and somatic alterations in other cysteines comprising the [4Fe4S] cluster and the four arginines that participate in hydrogen bonding to the cysteines coordinating the cluster[44] (Supplementary Tables 1 and 2) have been identified and are associated with colorectal as well as other cancers[7]. It is probable that these mutations also result in instability, degradation and dysfunction of the [4Fe4S] cluster secondary to the same mechanisms detailed above.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid containing GST-hMYH(65–350) was derived from pET19b-hMYH(65–350) [11] by PCR amplification using primers listed in Additional file 1: Table S1. The PCR product was digested with BamHI and XhoI and ligated into the digested pGEX-4T-2 (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%